Beyond the bulge–halo conspiracy? Density profiles of early-type galaxies from extended-source strong lensing. Issue 4 (7th March 2023) - Etherington, Amy; Nightingale, James W; Massey, Richard; Robertson, Andrew; Cao, XiaoYue; Amvrosiadis, Aristeidis; Cole, Shaun; Frenk, Carlos S; He, Qiuhan; Lagattuta, David J; Lange, Samuel; Li, Ran
ABSTRACT: Observations suggest that the dark matter and stars in early-type galaxies 'conspire' to produce a surprisingly simple distribution of total mass, ρ( r ) ∝ ρ −γ, with γ ≈ 2. We measure the distribution of mass in 48 early-type galaxies that gravitationally lens a resolved background source. By fitting the source light in every pixel of images from the Hubble Space Telescope, we find a mean $\langle \gamma \rangle =2.075_{-0.024}^{+0.023}$ with an intrinsic scatter between galaxies of $\sigma _\gamma =0.172^{+0.022}_{-0.032}$ for the overall sample. This is consistent with and has similar precision to traditional techniques that employ spectroscopic observations to supplement lensing with mass estimates from stellar dynamics. Comparing measurements of γ for individual lenses using both techniques, we find a statistically insignificant correlation of $-0.150^{+0.223}_{-0.217}$ between the two, indicating a lack of statistical power or deviations from a power-law density in certain lenses. At fixed surface mass density, we measure a redshift dependence, $\partial \langle \gamma \rangle /\partial z=0.345^{+0.322}_{-0.296}$, that is consistent with traditional techniques for the same sample of Sloan Lens ACS and GALaxy-Lyα EmitteR sYstems (GALLERY) lenses. Interestingly, the consistency breaks down when we measure the dependence of γ on the surface mass density of a lens galaxy. We argue that this is tentative evidence for an inflection point in the total mass-density profile at a few times the galaxy effective radius – breaking the conspiracy.